Supporting managerial intelligence tactics through information technology. (1st January 1999) - Sayeed, Lutfus; Brightman, Harvey J.
What tactics do managers use to identify emerging problems and opportunities? What are the impacts of information technology on the problem finding process? This study investigated the use of computer-based information and communications support in 90 problem and opportunity finding episodes within the banking industry. The technology permitted managers to use multiple stimuli and multiple problem finding tactics to identify emerging problems or opportunities. Furthermore, information technology allowed managers to use data external to the organisation to identify problems and opportunities. Managers were eight times more likely to use transaction-based processing systems and management information systems than decision support and executive support systems to identify problems and opportunities. Information technology tools supported problem finding by providing: (1) data to identify significant deviations from historical performance, budgets, or industry norms, and (2) timely communication among branch managers including uncovering potential criminal activity. The paper concludes with suggestions to enhance managerial intelligence activities through IS planning and possible research extensions.